The presence of KIR2DS5 confers protection against adult immune thrombocytopenia. Issue 3 (12th February 2014) - Seymour, L. A.; Nourse, J. P.; Crooks, P.; Wockner, L.; Bird, R.; Tran, H.; Gandhi, M. K.
<x xml:space="preserve">Abstract</x> Immune thrombocytopenia (ITP) is an autoimmune disorder of unknown aetiology, characterised by an isolated low platelet count in the absence of other identifiable causes. Genes influencing activation of the immune system have been identified as influencing predisposition. Killer cell immunoglobulin‐like receptors (KIR) control T‐cell and natural killer (NK) cell function via inhibitory and activating signalling pathways. The inhibitory KIR2DL3, KIR3DL2 and KIR3DL1 are up‐regulated in the T‐cells of patients with ITP in remission relative to those with active disease, and an association of KIR2DS2 and KIR2DL2 with ITP has also been reported. No comprehensive KIR analysis in ITP has been reported. We performed genotyping of all currently known KIR genes using sequence specific primer polymerase chain reaction (SSP‐PCR) on a cohort of 83 adult patients with ITP (chronic/persistent or relapsed primary ITP identified by defined criteria) and 106 age matched healthy white volunteers. Non‐white patients were not included in the analysis. There was an over‐representation of KIR2DS3 (known to be in linkage disequilibrium with KIR2DS2 and 2DL2) and under‐representation of KIR2DS5 (also protective against other immune mediated disorders) in adult ITP [odds ratio (OR) = 0.16, confidence interval (CI) 0.08–0.32, P < 0.001]. By multivariable binary logistic regression to adjust for age, sex and the effects of other KIR genes, the presence of KIR2DS2/2DL2 with KIR2DS5 abrogated the risk of KIR2DS2/2DL2 and the protective benefit of KIR2DS5. Further studies are required to establish the mechanistic basis for these observations and their potential impact on ITP therapy.